HAND1 loss-of-function within the embryonic myocardium reveals survivable congenital cardiac defects and adult heart failure. Issue 3 (9th July 2019) - Firulli, Beth A; George, Rajani M; Harkin, Jade; Toolan, Kevin P; Gao, Hongyu; Liu, Yunlong; Zhang, Wenjun; Field, Loren J; Liu, Ying; Shou, Weinian; Payne, Ronald Mark; Rubart-von der Lohe, Michael; et al.
Abstract: Aims: To examine the role of the basic Helix-loop-Helix (bHLH) transcription factor HAND1 in embryonic and adult myocardium. Methods and results: Hand1 is expressed within the cardiomyocytes of the left ventricle (LV) and myocardial cuff between embryonic days (E) 9.5–13.5. Hand gene dosage plays an important role in ventricular morphology and the contribution of Hand1 to congenital heart defects requires further interrogation. Conditional ablation of Hand1 was carried out using either Nkx2.5 knockin Cre ( Nkx2.5 Cre ) or α-myosin heavy chain Cre (α Mhc-Cre ) driver. Interrogation of transcriptome data via ingenuity pathway analysis reveals several gene regulatory pathways disrupted including translation and cardiac hypertrophy-related pathways. Embryo and adult hearts were subjected to histological, functional, and molecular analyses. Myocardial deletion of Hand1 results in morphological defects that include cardiac conduction system defects, survivable interventricular septal defects, and abnormal LV papillary muscles (PMs). Resulting Hand1 conditional mutants are born at Mendelian frequencies; but the morphological alterations acquired during cardiac development result in, the mice developing diastolic heart failure. Conclusion: Collectively, these data reveal that HAND1 contributes to the morphogenic patterning and maturation of cardiomyocytes during embryogenesis and although survivable, indicates a role for Hand1 within the developing conduction system and PM development.